Relational Andean Spiritualities - Chipana Quispe, Sofia Nicolasa (2022)
The text-textile presents the interrelation of Andean ancestral wisdoms and spiritualities, which are intertwined with each other, forming a living fabric of reciprocal links that restore balance and harmony, based on relationships of mutuality and correspondence, which enables the reconstitution and interaction of the Community of Life, the Ayllu, in which various beings coexist, from which the jaq’e, the person linked to their ancestry, sustains their resistance and re-existence from the upbringing of the Good Living.